Elevated serum levels of IL-2R, IL-1RA, and CXCL9 are associated with a poor prognosis in follicular lymphoma - Mir, Muhammad A. (Blood, 2015)
Serum cytokines and chemokines may reflect tumor biology and host response in follicular lymphoma (FL). To determine whether the addition of these biological factors may further refine prognostication, 30 cytokines and chemokines were measured in pretreatment serum specimens from newly diagnosed FL patients (n = 209) and from 400 matched controls. Cytokine levels were correlated with clinical outcome in patients who were observed or received single agent rituximab, or those who received chemotherapy. Correlations with outcome in chemotherapy treated patients were further examined in a separate cohort of 183 South West Oncology Group (SWOG) patients and all patients were then included in a meta-analysis. Six cytokines were associated with outcome in the Molecular Epidemiology Resource (MER) after adjusting for the FL international prognostic index. In patients who were observed or treated with rituximab alone, increased serum IL-12 and interleukin 1 receptor antagonist (IL-1RA) (P = .005 and .02) were associated with a shorter event-free survival. In patients receiving chemotherapy, hepatocyte growth factor, IL-8, IL-1RA, and CXCL9 (P = .015, .048, .004, and .0005) predicted a shorter EFS. When the MER chemotherapy treated patients and SWOG patients were combined in a meta-analysis, IL-2R, IL-1RA, and CXCL9 (P = .013, .042, and .0012) were associated with a poor EFS.